Developing Oral Fluency among Sudanese EFL Learners at University Level - Mohammed, Muntasir; Bakri, Mohammed; Ahmed, Ienas (Gezira Journal of Educational Sciences and Humanities; مجلد 15 عدد 1 (2018), 2018)
This study aims at eliciting  university teacher's views on the use of phrases as a means of developing oral fluency skills for English learners and to show the importance of language function, context and authentic situations to develop and promote oral fluency skills in Sudanese EFL learners at university level. To achieve the objectives, the study used a questionnaire in order to address the study questions and objectives.100 employed teachers participated in the questionnaire. The Study found out that the teachers have positive views towards using phrases inside and outside the lecture rooms so as to enhance the students  oral fluency skill  in using the target language as well as to take care of the language forms to avoid imperfect use of the language.